Characterization of the response to drought of segregating lines of corn - Sánchez, Elizabeth Ibarra; Castillo Gutiérrez, Antonio; Valdez, María Eugenia Nuñez; Rodríguez, Ramón Suárez; Rodríguez, María Andrade; Roldán, Francisco Perdomo (Revista Mexicana de Ciencias Agrícolas, 2020)
Drought stress is one of the main causes of the reduction in maize yield in the tropics, mainly in agriculture that depends on rain, which requires the generation of genotypes with tolerance to drought. The objectives of the research were to quantify the agronomic response of a group of segregating S2 lines of corn in irrigated and drought environments, as well as to select lines with tolerance to water deficit, based on two indices and the average yield of both environments. The study genotypes were 96 segregating S2 lines, two control lines and two lines not selected for drought. The lines were evaluated under irrigation and induced drought using a Latice Alpha design with four replications, in Ayala, Morelos, Mexico. 10 morphological variables were measured and drought susceptibility indices (ISS) and tolerance index (IT) were estimated. Based on the grain yield in irrigation (3.14 t ha-1), a reduction of 77.7% of the yield in drought (0.7 t ha-1) was observed. The ISS and IT indices identified the LUM69, LUM82 and LUM30 lines as drought tolerant, only LUM69 showed a competitive yield in both environments. The ISS and IT index as criteria to identify tolerant genotypes did not select the lines with the best grain yield under irrigation conditions, so the average yield through moisture environments should be included in the selection criteria.
Keywords: drought tolerance; susceptibility indices; S2 lines